Intergenerational Family Relations: An Evolutionary Social Science Approach (2018)
This book offers a synthesis of social science and evolutionary approaches to the study of intergenerational relations, using biological, psychological and sociological factors to develop a single framework for understanding why kin help one another across generations. With attention to both biological family relations as well as in-law and step-relations, it provides an overview of existing studies centred on intergenerational relations – particularly grandparenting – that incorporate social science and evolutionary family theories. This evolutionary social science approach to intergenerational family relations goes well beyond the traditional nature versus nurture distinction. As such, it will appeal to scholars across a range of disciplines with interests in relations of kinship, the lifecourse and the sociology of the family.